Guillain-Barré syndrome after bortezomib therapy in a child with relapsed acute lymphoblastic leukemia. (17th February 2022) - Ceolin, Valeria; Cenna, Rosita; Resente, Francesca; Spadea, Manuela; Fagioli, Franca; Bertorello, Nicoletta
ABSTRACT: A 12-year-old male being treated for a high-risk relapsed T-acute lymphoblastic leukemia presented progressive weakness and numbness of both legs after having received a chemotherapy regimen that included bortezomib. Diagnosis of acute Guillain-Barré syndrome-like inflammatory demyelinating polyneuropathy was made following clinical examination, cerebrospinal fluid analysis, electrodiagnostic studies, magnetic resonance imaging, and serum immunoglobulin antibodies to anti-ganglioside. Intravenous immunoglobulin treatment was started, resulting in complete clinical recovery. Although in rare cases, Guillain-Barré syndrome after bortezomib therapy has been reported; this paper suggests that GBS may occur when bortezomib is administered and high‑dose intravenous immunoglobulin lead to a resolution of the symptoms.